160 likes | 299 Views
The water in a swimming pool decreases two degrees every hour. How much has the water temperature changed after five hours?. In this lesson you will learn about multiplication with positive and negative integers by noticing patterns. Integers include 12 0 And their opposites
E N D
The water in a swimming pool decreases two degrees every hour. How much has the water temperature changed after five hours?
In this lesson you will learn about multiplication with positive and negative integers by noticing patterns.
Integers include • 12 0 And their opposites -5 -12 0 Multiplication can be written using: 4 · 6 4 x 6 (4)(6)
The meaning of multiplication does not change, we just need to consider the types of numbers we are multiplying. 5 x -2 x -2 -6.5 x 3.4
Let’s take a look at a multiplication pattern…. 5 x 4 = 20 5 x 3 = 15 5 x 2 = 10 5 x 1 = 5 5 x 0 = 0 5 x(-1)=-5 5 x(-2)=-10
Let’s review the pattern… 5 x 4 = 20 5 x 3 = 15 5 x 2 = 10 5 x 1 = 5 5 x 0 = 0 5 x(-1)= -5 5 x(-2)= -10 One fewer and going down 5 each time… Leads to negative product here.
Let’s continue the pattern…. 5 x(-2) = -10 4 x(-2) = -8 3 x(-2) = -6 2 x(-2) = -4 1 x (-2) = -2 0 x(-2) = 0 (-1) x (-2)= +2 (-2) x (-2)=+4
Let’s review the pattern…. 5 x (-2) = -10 4 x (-2) = -8 3 x (-2) = -6 2 x (-2) = -4 1 x (-2) = -2 0 x (-2) = 0 (-1) x(-2)= 2 (-2) x(-2)= 4 One fewer and going up 2 each time… Leads to positive product here.
(-1) x (-2) = -2 (-1) x (-2) = +2
If the temperature rises…. 5 x 2 = 10 degrees If the temperature does not change 5 x 0 = 0 degrees If the temperature falls….. 5 x -2 = -10 degrees
The water in a swimming pool decreases two degrees every hour. How much has the water temperature changed after five hours? 5 x -2= -10 degrees
In this lesson you have learn about multiplication with positive and negative integers by noticing patterns.
Find the product: (-4) x 3 = (-4) x (-3) = -12 +12
Without solving determine if the answer is positive or negative: • 34(-23) -34(-23) -34(-23)(-29)
Find the product of: • (-23) x (-34)
Find the product: (-4) x 6 = (-4) x (-2) =